2002
DOI: 10.1063/1.1425428
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionally dependent tensor identities by double antisymmetrization

Abstract: Some years ago, Lovelock showed that a number of apparently unrelated familiar tensor identities had a common structure, and could all be considered consequences in n-dimensional space of a pair of fundamental identities involving trace-free (p, p)-forms where 2p ≥ n. We generalise Lovelock's results, and by using the fact that associated with any tensor in n-dimensional space there is associated a fundamental tensor identity obtained by antisymmetrising over n + 1 indices, we establish a very general 'master'… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
78
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(84 citation statements)
references
References 26 publications
(63 reference statements)
2
78
1
Order By: Relevance
“…which is divergence free and identically zero in 4 dimensions giving us in this case the first Lovelock identity (for extensions see for example [14][15][16]. In four dimensions the action involving the Gauss Bonnet invariant when coupled with a scalar field is no longer a topological invariant.…”
Section: Introductionmentioning
confidence: 99%
“…which is divergence free and identically zero in 4 dimensions giving us in this case the first Lovelock identity (for extensions see for example [14][15][16]. In four dimensions the action involving the Gauss Bonnet invariant when coupled with a scalar field is no longer a topological invariant.…”
Section: Introductionmentioning
confidence: 99%
“…Much earlier, Lovelock [14] had pointed out that a number of apparently unrelated results were all really consequences of a class of identities which he christened dimensionally dependent identities -identities which are a trivial, but subtle, consequence of dimension alone. Recently Edgar and Höglund [15] have generalised Lovelock's results, and demonstrated that the underlying principle in all of these investigations in [6 -13], and some new ones, was the explicit exploitation of dimensionally dependent identities. Furthermore, in algebraic Rainich theory, Bergqvist and Höglund [16] have exploited these ideas further, and obtained results in five dimensions involving cubic terms in the energy momentum tensor -motivated by the familiar results in four dimensions involving quadratic terms, [17]; while Edgar and Höglund [18] have demonstrated the crucial role that dimensionally dependent identities play in the existence of the Lanczos potential for the Weyl tensor in different dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…In four dimensions, obviously it cannot be sufficient simply to substitute n = 4, since we know from the spinor version that the right hand side must disappear completely in four dimensions. But if we consider the 4-dimensional fddi [14,15] (quoted in Lemma 3 at the end of this section), we find that, when contracted with L de f , we obtain the ddi,…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations